Mind and Spirit: a comparative theory about representation of mind and the experience of spirit. (25th March 2020) - Luhrmann, T.M.
Abstract: This special issue reports the findings of the Mind and Spirit project. We ask whether different understandings of 'mind', broadly construed, might shape the ways that people attend to and interpret thoughts and other mental events – and whether their judgements affect their experience of (what they take to be) gods and spirits. We argue in this collection that there are indeed cultural differences in local theories of minds, in the way social worlds draws the line between interior and exterior, and that these differences do affect the way people sense invisible others. This introduction lays out the ideas that inspired the project and the methods that we used. This is the first report on our work. Abstrait: Esprit et esprit(s) : une théorie comparative de la représentation de l'esprit et de l'expérience des êtres spirituels Résumé Ce dossier rassemble des contributions au projet « Esprit et Esprit(s) » dont l'objet porte sur la question de savoir si différentes acceptions du mot « esprit » ( mind ), au sens large, peuvent modeler la manière dont les pensées et autres données mentales sont vécues et interprétées, et si ces jugements affectent la perception des entités considérées comme des divinités et des esprits. Il existe bel et bien des différences culturelles dans les théories locales de l'esprit, selon la manière dont les mondes sociaux délimitent l'intérieur et l'extérieur, et ces différences affectent la manière dont les « autres » invisibles sont perçus. Cette introduction expose les idées qui ont inspiré le projet et les méthodes utilisées. Il s'agit d'un premier compte‐rendu des travaux menés dans ce cadre.